Philippine Education in the Modern World: A Trench for Global Academic Success or another Year of Educational Failure? - Lorie Mae P Coloquit (Journal of English Education and Linguistics, 2020)
This essay aims to identify and analyse perennial and current problems that need to be improved in Philippine education. For many years, education is believed to be the key to outsmart poverty and other economic issues (Butuyan, 2016). However, for the decades, the country’s educational system remains challenged by perennial issues which continue to escalate as the number of students increases each year that contributes to more societal dilemmas. Despite all this, the nation’s educational system has been withstanding several issues through initiating various interventions in accordance to its means of delivering quality education, allocating manageable tasks for teachers, and bringing forth calibre benchmarks that could lead the country out of the global academic ignominy. Thus, for the Philippines to attain its academic and economic goals, further research should be conducted not only to realize the cause of the issues but to contribute a better solution to each problem.